2016
DOI: 10.21037/jgo.2016.09.10
|View full text |Cite
|
Sign up to set email alerts
|

Advanced biliary tract cancer: clinical outcomes with ABC-02 regimen and analysis of prognostic factors in a tertiary care center in the United States

Abstract: Background: Gemcitabine plus cisplatin (GC) is currently the standard regimen for advanced biliary tract cancers (BTC) based on the outcomes in ABC-02 trial. Multiple factors can affect outcomes in these patients. This retrospective review evaluates the University of Cincinnati experience with GC in advanced intrahepatic (IHC)/ extrahepatic cholangiocarcinoma (EHC) and gall bladder carcinoma (GBC). Methods: In this study approved by University of Cincinnati IRB, retrospective analysis of advanced BTC patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
(77 reference statements)
2
10
1
Order By: Relevance
“…In contrast with a recent similar retrospective analysis in 26 metastatic BTC patients [14], we observed a difference in OS in patients treated with gemcitabine and cisplatin in daily practice compared with patients in the ABC-02 trial. Almost half of these patients [14] (49%) received second or third line chemotherapy, which may explain the higher OS in the other retrospective analysis (9.5 vs. 10.5 months).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with a recent similar retrospective analysis in 26 metastatic BTC patients [14], we observed a difference in OS in patients treated with gemcitabine and cisplatin in daily practice compared with patients in the ABC-02 trial. Almost half of these patients [14] (49%) received second or third line chemotherapy, which may explain the higher OS in the other retrospective analysis (9.5 vs. 10.5 months).…”
Section: Discussioncontrasting
confidence: 99%
“…Although PS is a somewhat subjective and vague assessment of the physical condition of cancer patients, it was identified as the most important predictor of the survival in advanced BTC patients receiving chemotherapy. Indeed, some previous studies have also reported PS as a prognostic factor in patients with advanced BTC, in conformity with our findings [811, 13, 14, 1621]. Although previous reports suggest a poor prognosis in patients with PS 2 [8, 10, 11, 17, 18, 21], both patients with PS 2 and PS 1 had a poor prognosis in this study.…”
Section: Discussionsupporting
confidence: 93%
“…1,3 If surgical tumor resection is not feasible, chemotherapy with gemcitabine and cisplatin represents the standard of care, resulting in a median overall survival (OS) of 10-12 months. [4][5][6] Importantly, the postoperative outcome following BTC resection is very heterogeneous and the majority of successfully resected patients (R 0 resection) face disease recurrence, 7 resulting in an overall 5-year survival rate of less than 30%. [8][9][10] Moreover, while current data suggest a benefit of more aggressive adjuvant treatment regimens in pancreatic cancer, which shares many clinicopathological similarities with BTC, 11 data from lager clinical trials evaluating this concept in patients with BTC are still missing (NCT02170090).…”
Section: Introductionmentioning
confidence: 99%